Дослідження компонентного складу та протимікробної активності ефірної олії з суцвіть Tagetes patula L. - Малюгіна, Олена Олександрівна; Мазулін, Олександр Владиленович; Буряк, Валерій Прокопович; Єренко, Олена Костянтинівна; Смойловська, Галина Павлівна; Мазулін, Георгій Владиленович; Malugina, O. O.; Mazulin, O. V.; Burak, V. P.; Yerenko, O. K.; Smojlovska, G. P.; Mazulin, G. V. (Study of the composition and antimicrobial activity of the essential oil from inflorescences of Tagetes patula L., 2014)
Визначено кількісний вміст та якісний склад ефірної олії суцвіть Tagetes patula L. nana varietes «Goldkopfen». За допомогою хромато-мас-спектрометричного методу ідентифіковано до 22 компонентів, 8 з яких – вперше, визначено їх вміст у досліджуваній олії. Визначено фізико-хімічні показники ефірної олії, досліджено її протимікробну та протигрибкову активність. Ефірна олія з суцвіть T. patula L. nana var. «Goldkopfen» виявляє виражену протимікробну та протигрибкову дію на Staphylococcus aureus (АТСС 25923), S. aureus (клін.), Klepsiella pneumonia (клін.), Staphylococcus saprophytus (клін.), Candida albicans (АТСС 885653) (клін.). The aim of this scientific work is to determine physicochemical properties, quantitative content and composition of the essential oil from inflorescences of Tagetes patula L. nana var. «Goldkopfen» and its antimicrobial and antifungal activity. We have chosen the essential oil from inflorescences of T. patula L. nana var. «Goldkopfen» as an object of our study. Plant material was harvested during the flowering period in 2013. The essential oil was obtained from inflorescences by Clevenger method. We identified components of the essential oil and determined their quantitative content by gas-liquid chromatography method using «Agilent Technology 6890N/5973N» chromatograph. Chromatograms were identified with the help of NIST02 massspectra library. We studied antimicrobial activity by agar diffusion method with paper discs. We discovered that there were up to 22 compounds present in the composition of the essential oil. The quantitative content of these components was determined. 8 compounds were discovered for the first time. We identified that the main compounds of the essential oil are: spathulenol ((367.70±9.33) mg/kg), piperitenone ((96.70±0.39) mg/kg), p-cymene-8-ol ((73.50±0.30) mg/kg), piperitone ((51.10±0.26) mg/kg), β-сary ophyl lene ((36.60±0.02) mg/kg), squalene ((32.60±0.16) mg/ kg), myristic acid ((26.90±0.12) mg/kg), piperitenone oxide ((25.70±0.01) mg/kg), nonacosane ((22.70±0.11) mg/kg), tricosane ((20.10±0.12) mg/kg). We determined that the es sential oil from inflorescences of T. patula L. nana «Goldkopfen» has antimicrobial and antifungal activity against Staphylococcus aureus (АТСС 25923), S. aureus (clin.), Klepsiella pneumonia (clin.), Staphylococcus saprophytus (clin.), Candida albicans (АТСС 885653) (clin.).
Keywords: ефірна олія; чорнобривці розлогі; протимікробна дія; протигрибкова дія; essential oil; French marigold (Tagetes patula); antimicrobial activity; antifungal activity